The Relational Fabric of Community - Bessant, Kenneth C. (Palgrave Macmillan US, 2018)
Theoretical and philosophical work on community has yielded multifold definitions and analytical frameworks. Kenneth C. Bessant reflects on the inherent complexity and diversity of this deeply intersubjective aspect of lived social experience. He explores the relational underpinnings of early and more contemporary approaches to the study of community, with a particular emphasis on their core assumptions, concepts, and tenets. Each of these perspectives offers a relatively distinct interpretation of community, while also revealing the intrinsically relational fabric of its perpetual emergence, dynamism, and transformation. The 'being-with' of relational social existence is the fundamental basis upon which all conceptions of community are built, and this is the epicenter around which the book revolves. Community is born of, exists within, and brings forth social relations. It is a living expression of relational willing, thinking, and acting.